Obligatory Phenomenon in the Old Arabic Proverbs - Khalaf, Qays Allawi (Journal of Tikrit University for Humanities, 2020)
The research talks about the obligatory phenomenon in the old Arabic proverbs in the pre-Islamic era and the Islamic era and the proverbs generated in the Abbasid era. This phenomenon is manifested through the linguistic dimension that includes the grammatical and morphological side and through the literary dimension that includes the obligatory formulation that is set for the proverb and the metaphor that must be stood in and appeared the phenomenon of the obligation in pre-Islamic proverbs is more clear.. The research contains another phenomenon, that is the commitment phenomenon that characterized the Abbasid era in terms of the commitment of these proverbs to linguistic methods that were popular during that era.